1987
DOI: 10.1159/000226443
|View full text |Cite
|
Sign up to set email alerts
|

Complete Remission following Endocrine or Combined Cytotoxic and Hormonal Treatment in Advanced Breast Cancer

Abstract: Among 422 patients with advanced breast cancer treated in a randomized trial we observed 60 complete responses (CR). Sixteen were achieved among 206 patients treated with endocrine therapy alone and 37 among 216 patients treated with concomitant chemotherapy and endocrine therapy. The incidence of CR in women treated with the concomitant modality was higher in those with dominant soft tissue disease, intermediate in those with osseous or pulmonary involvement, and low in patients with liver metastases. Bone wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 12 publications
2
3
1
Order By: Relevance
“…Other studies confirmed this finding [5, 6], although the majority of patients were chemo-naïve. Consequently, it is difficult to translate the concept of curability of a minority of MBC patients in an era in which nearly all patients have previously received adjuvant cytotoxic therapy.…”
Section: Introductionsupporting
confidence: 62%
“…Other studies confirmed this finding [5, 6], although the majority of patients were chemo-naïve. Consequently, it is difficult to translate the concept of curability of a minority of MBC patients in an era in which nearly all patients have previously received adjuvant cytotoxic therapy.…”
Section: Introductionsupporting
confidence: 62%
“…Despite various modalities in the therapeutic approach to advanced breast cancer, the incidence of CR is generally lower than observed in our study [2]. However, the presence of a CR does improve the prognosis of the disease [2]. The high percentage of CR in our study further supports the conclusions of our previous report [1] on the importance of performing the hormone test for a rational indication for ovariectomy, not only in cases of advanced carcinoma but also as adjuvant therapy.…”
Section: Discussionsupporting
confidence: 85%
“…Despite various modalities in the therapeutic approach to advanced breast cancer, the incidence of CR is generally lower than observed in our study [2]. However, the presence of a CR does improve the prognosis of the disease [2].…”
Section: Discussioncontrasting
confidence: 61%
“…16,20,21 Interestingly, most of what is known about medical induction of tumor dormancy regards hormone-related interventions; long-term cytostatic effects on tumors have been achieved by hormone withdrawal in selected groups of cancer patients. 22 The immune system, through either antibody or cell-mediated effectors, can readily contribute to induce and maintain microscopic tumors dormant, especially in lymphoma models. 23,24 Cytotoxic T cells can restrain tumor growth through both cytolytic mechanisms and release of certain cytokines, including IL-2 and IFN-γ; 25,26 moreover, anti-idiotype antibodies have been found to bind B lymphoma cells and signal both cell cycle arrest and apoptosis.…”
mentioning
confidence: 99%